Comparing Patient Satisfaction and Intubating Conditions Using Succinylcholine or Low-Dose Rocuronium for Rigid Bronchoscopy: A Randomized Study - Ghezel-Ahmadi, Verena; Ghezel-Ahmadi, David; Mangen, Jacques; Bolukbas, Servet; Welker, Andreas; Kuerschner, Veit Christian; Fischer, Andreas; Schirren, Joachim; Beck, Grietje (The Thoracic and Cardiovascular Surgeon, 2015)
Introduction Despite its serious side effects, succinylcholine is commonly used for neuromuscular relaxation in short procedures, such as rigid bronchoscopy and tracheobronchial interventions. The application of low-dose rocuronium reversed by low-dose sugammadex might be a modern alternative. The aim of this study was to compare patient satisfaction, incidence of postoperative myalgia (POM) as well as intubating conditions of these two muscle relaxants for rigid bronchoscopy.Methods and Materials A single-center, prospective-randomized, blinded study of 95 patients, scheduled for rigid bronchoscopy and tracheobronchial intervention was conducted. The patients were anesthetized with propofol, remifentanil and either low-dose succinylcholine (S) (0.5 mg/kg) or low-dose rocuronium (0.25 mg/kg) with sugammadex (RS) (0.5 mg/kg). All patients were evaluated on the first and second postinterventional day for their satisfaction with the treatment (rigid bronchoscopy) using a Numeric Analog Rating Scale (NAS 0–10) and the presence and severity of POM (NAS 1–4). Intubating conditions were assessed as excellent, good, or poor on the basis of position of vocal cords and reaction to insertion of the rigid bronchoscope.Results Patients in the S group were less satisfied with the treatment than patients in RS group (72.7 vs. 93.7%, p = 0.007). The incidence of POM on the first day after intervention was significantly higher in the S group then in the RS group (56.9% vs. 4.3%, p < 0.001). Although the intubation was faster (p < 0.001) and the intubating conditions significantly superior (p < 0.003) with succinylcholine, acceptable conditions were also achieved with low-dose rocuronium in 75% of patients. The anesthetic drug costs were significantly higher in the RS group then in the S group (p < 0.001).Conclusion The results suggest that low-dose rocuronium provided better patient satisfaction and less POM. But with the use of low-dose succinylcholine, the intubating conditions are more comfortable, and it is less expensive than rocuronium/sugammadex.
Keywords: anesthesia; airway; health economics; pharmacology; quality of life